Two Derivative Spectrophotometric Methods for the Simultaneous Determination of 4-AminoAntipyrine in Presence of Its Acidic Products - Fahmi Abbas, Ruba (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Simple, economic and sensitive mathematical spectrophotometric methods were developed for the estimation 4-aminoantipyrine in presence of its acidic product. The estimation of binary mixture 4-aminoantipyrine and its acidic product was achieved by first derivative and second derivative spectrophotometric methods by applying zero-crossing at (valley 255.9nm and 234.5nm) for 4-aminoantipyrine and (peak 243.3 nm and 227.3nm) for acidic product. The value of coefficient of determination for the liner graphs were not less than 0.996 and the recovery percentage were found to be in the range from 96.555 to 102.160. Normal ratio spectrophotometric method 0DD was used 50 mg/l acidic product as a divisor and then measured at 299.9 nm with correlation coefficient 0.998 and limit of detection 0.04098. ratio derivative methods 1DD and 2DD; are based on measuring the first derivative and second derivative for normal ratio spectrum at (peak 290.7 nm and valley 310 nm) for 1DD and (peak 286, valley 301 and peak 316nm) for 2DD the correlation coefficient for linearity graph not less than 0.997 and the recovery percentage were found to be in the range from 99.64 to 100.11.